Digital Transparency and Firm Value: Their Influence on Voluntary Disclosure in Indonesian Companies - Nursulistyo, Emy Dwi; Arifna Putri, Ade Aisya (International Journal of Natural Science and Engineering, 2025)
Voluntary disclosure is an essential aspect for companies to measure sustainability and corporate responsibility for the environment. This study aims to examine whether there is an influence between firm value and the availability of the company's website on voluntary disclosure. The population in this study are all companies listed on the Indonesia Stock Exchange (IDX) in 2024 with purposive sampling. Observation data amounted to 92 non-financial companies. Data were collected from the company's financial statements and annual reports. Multiple regression tests were used to analyze this research. The results showed that the presence of firm value and company website has a significant effect on voluntary disclosure. This finding indicates that firm values and company websites influence voluntary disclosure. Digital transparency has a significant role in encouraging voluntary disclosure by firms in Indonesia; increased digital transparency not only strengthens stakeholder trust but also positively contributes to increased firm value. In conclusion, digital transparency significantly increases firm value through a positive influence on the level of voluntary disclosure. The findings suggest that companies in Indonesia that effectively implement digital transparency tend to be more open in disclosing information, thereby strengthening investor confidence and improving corporate reputation. The implication is that increased digital transparency may encourage companies in Indonesia to make more extensive and accurate voluntary disclosures. This ultimately contributes to increased firm value through the creation of investor confidence and information efficiency in the market.